Real-time infrared spectroscopy coupled with blind source separation for nuclear waste process monitoring - Crouse, Steven H.; Kocevska, Stefani; Noble, Sean; Prasad, Rupanjali; Howe, Anthony M.; Lambert, Dan P.; Rousseau, Ronald W.; Grover, Martha A. (Frontiers in Nuclear Engineering, 2023)
On-line infrared absorbance spectrometry enables rapid measurement of solution-phase molecular species. Many spectra-to-concentration models exist for spectral data, with some models able to handle overlapping spectral bands and nonlinearities. However, model accuracy is limited by the quality of training data used in model fitting. The process spectra of nuclear waste simulants at the Savannah River Site display incongruity between training and process spectra; the glycolate spectral signature in the training data does not match the glycolate signature in Savannah River National Laboratory process data. A novel blind source separation algorithm is proposed that preprocesses spectral data so that process spectra more closely resemble training spectra, thereby improving model quantification accuracy when unexpected sources of variation appear in process spectra. The novel blind source separation preprocessing algorithm is shown to improve nitrate quantification from an R 2 of 0.934 to 0.988 and from 0.267 to 0.978 in two instances analyzing nuclear waste simulants from the Slurry Receipt Adjustment Tank and Slurry Mix Evaporator cycle at the Savannah River Site.